2023
DOI: 10.5194/wes-8-289-2023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring limiting factors of wear in pitch bearings of wind turbines with real-scale tests

Abstract: Abstract. Oscillating movements under load can cause wear in rolling bearings. Blade bearings of wind turbines are subject to both. To know how to avoid wear in these bearings is important since they ensure the operational safety of the turbine. Oscillations of blade bearings vary in load, speed, and amplitude. The objective of this work is to find limits of these operating parameters with regards to wear occurrence. To this end several tests with real-size bearings were carried out. The test parameters are ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…BEHNKE ET AL. also showed results of the wear tests of real-size blade bearings with the same grease as the lubricant [5]. For the smaller amplitude ratios, the wear already occurred for only 1000 cycles, which matches the fast wear initiation obtained in the tests with the type 7220 bearings in this paper.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…BEHNKE ET AL. also showed results of the wear tests of real-size blade bearings with the same grease as the lubricant [5]. For the smaller amplitude ratios, the wear already occurred for only 1000 cycles, which matches the fast wear initiation obtained in the tests with the type 7220 bearings in this paper.…”
Section: Discussionsupporting
confidence: 84%
“…At a more advanced stage, after 80,000 cycles, the damage pattern shown in Figure 5c appears. Some parts of the wear mark still appear reddish-brown and on the left side at middle height a bigger material spall can be observed (5). It is also noticeable that large parts of the damage mark have been smoothed and have a mirror-like appearance (4).…”
Section: Wear Development 7208mentioning
confidence: 99%
See 2 more Smart Citations
“…Tests on small-scale bearings showed that interrupting oscillating and wear-critical movements with lubrication runs effectively prevents wear. This was even tested and verified for real-scale blade bearings with about 5 m diameter Behnke and Schleich, 2023). In general, two different types of lubrication runs can be differentiated.…”
Section: Introductionmentioning
confidence: 89%